Blank Cheques Commercial Law Perspective - Haykal Rizal (International Asia Of Law and Money Laundering, 2022)
Cheques are one of the Securities Regulated in the Commercial Law Code, the use of cheques is increasing day by day, cheques as a means of payment is very beneficial for the issuer, because this check gives a sense of security for the issuer who issued the check and also the issuer can issue a check backwards if at the time the issuer issued the check, the funds in the bank is not enough. But in practice, there is often abuse of check issuance by issuing blank checks. By issuing a blank cheque will result in the issuer's account will be closed and reporting to Bank Indonesia, and the issuer's account should not be associated banks and may also be subject to criminal acts of fraud.